2022
DOI: 10.1186/s12886-022-02440-9
|View full text |Cite
|
Sign up to set email alerts
|

Development pattern of ocular biometric parameters and refractive error in young Chinese adults: a longitudinal study of first-year university students

Abstract: Background The increase in the prevalence of myopia has become a matter of serious public health concern, and few studies to date have examined the ocular biometric parameters of myopia in young Chinese adults. This study aimed to investigate the longitudinal ocular biometric and refractive development of first-year university students and the influence of near work. Methods This study included 526 first-year university students from Tianjin Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
2
1
Order By: Relevance
“…The association between more time spent reading, longer AL and a more myopic SER found in 7‐ to 9‐year‐olds in Singapore contrast with the present study, where no association between ocular biometric parameters and time spent reading was found 39 . However, more recent studies demonstrated that increased screentime and time spent engaged in online gaming was associated with a longer AL and myopic SER in 18‐year‐olds 40 . Moreover, the association between increased screentime, a higher AL/CR and more myopic SER found in the present study aligns with objectively measured smartphone use in Dutch 13‐year‐olds, 16 where continuous use during schooldays was positively associated with AL/CR and negatively associated with SER.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The association between more time spent reading, longer AL and a more myopic SER found in 7‐ to 9‐year‐olds in Singapore contrast with the present study, where no association between ocular biometric parameters and time spent reading was found 39 . However, more recent studies demonstrated that increased screentime and time spent engaged in online gaming was associated with a longer AL and myopic SER in 18‐year‐olds 40 . Moreover, the association between increased screentime, a higher AL/CR and more myopic SER found in the present study aligns with objectively measured smartphone use in Dutch 13‐year‐olds, 16 where continuous use during schooldays was positively associated with AL/CR and negatively associated with SER.…”
Section: Discussioncontrasting
confidence: 99%
“…39 However, more recent studies demonstrated that increased screentime and time spent engaged in online gaming was associated with a longer AL and myopic SER in 18-year-olds. 40 Moreover, the association between increased screentime, a higher AL/CR and more myopic SER found in the present study aligns with objectively measured smartphone use in Dutch 13-year-olds, 16 where continuous use during schooldays was positively associated with AL/CR and negatively associated with SER.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence myopia among students in eastern cities is generally higher, with two cities in Jiangsu Province reporting prevalence rates of 86.8% for high school students (11,30). The prevalence of myopia among adolescents in some northern cities was even above 90%, with the prevalence of high myopia reaching more than 20% (32,33,36,37). In contrast, myopia prevalence is relatively low in some western and minority regions such as Xinjiang, with 80.5% of adolescents aged 14 to 18 (38).…”
Section: Discussionmentioning
confidence: 98%
“…Asia [4]. The prevalence of high myopia in university students in East Asia was 16%-28% in recent studies [39,40]. Preventing moderate myopia progression to high myopia has become an important research issue [18].…”
Section: Discussionmentioning
confidence: 99%